1994
DOI: 10.3109/02652049409034992
|View full text |Cite
|
Sign up to set email alerts
|

A lymphotropic colloidal carrier system for diethylcarbamazine: Preparation and performance evaluation

Abstract: Targeting to organs other than the RES-bearing organs is difficult to achieve. A nanoparticle-based emulsion delivery system was prepared and its efficacy in enhancing the lymphatic uptake of the anti-filarial drug diethylcarbamazine was evaluated. It was compared with a simple w/o emulsion and a control aqueous solution. The effect of route of administration on the lymphatic uptake was studied and it was found that the i.p. route gave better results as compared to the i.v. route, in which total lack of lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A consistent finding in these studies is that the colloidal particles administered interstitially are mainly taken up by the regional lymphatic system and accumulate to varying degrees in the lymph nodes. This unique selective biodistribution led to the development of lymphatic targeting drug delivery systems utilizing colloidal materials as drug carriers, such as liposomes [8][9][10], activated carbon particles [11,12], emulsions [13,14], lipids [15] and various polymeric particulates [16,17]. However, lymphatic distribution of particles of different materials and sizes following intrapleural administration has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A consistent finding in these studies is that the colloidal particles administered interstitially are mainly taken up by the regional lymphatic system and accumulate to varying degrees in the lymph nodes. This unique selective biodistribution led to the development of lymphatic targeting drug delivery systems utilizing colloidal materials as drug carriers, such as liposomes [8][9][10], activated carbon particles [11,12], emulsions [13,14], lipids [15] and various polymeric particulates [16,17]. However, lymphatic distribution of particles of different materials and sizes following intrapleural administration has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of nanocarrier technology such as polymeric nanoparticles, lipid based nanoparticles, and liposomes are high stability, high loading capacity, ability to protect and to encapsulate hydrophobic and hydrophilic drugs, feasibility of variable administration routes, possibility to targeting, and control of drug release rate. Additionally nanocarrier system may improve drug bioavailability, reduce systemic side effects, and increase efficiency of drug therapies (Luo et al, 2010;Paliwal et al, 2009;Ling et al, 2006;Karajgi and Vyas, 1994;Parker et al, 1981). On the other hand, the studies that identify the important physicochemical factors affecting lymphatic delivery of carrier have been carried out.…”
mentioning
confidence: 99%
“…Hashida et al (1977; developed gelatin spheres in oil (S/O) emulsion for minimizing the instability of the W/O emulsion. The nanoparticle-in-oil emulsion system, containing anti-filarial drug in gelatin nanoparticles, was studied for enhancing lymphatic targeting (Karajgi and Vyas, 1994), and it was suggested that this colloidal system held excellent potential as a lymphotropic carrier system. More recently, an emulsion formulation consisting of an anticancer drug, Pirarubicin, and Lipiodol was developed to treat cancer and metastatic lymph nodes (Yoshimura and Nunomura, 1996).…”
Section: Introductionmentioning
confidence: 99%